(3GdeSGdc hGdeeGdcs - (3GdMSjf Hf CMeO GdegdHjs
(3ChdgG (B:s
(3bGd eMeO Hf GdMSf GdcdGYi bQCJ ai cJGH GdeSGdc hGdeeGdc GdYRjRi JCdja GdMSf Hf CMeO GdegdHi UaI HjJ GdebOS s
(3BNQgG (B:s
(3eOjfI dWjaI CTHg GdHdGO HecI dCfgG Hjf LHdjf hef ChO YTJ Edi ZGjI HVYI YTQ jhekG hef ZGjI Edi TGeI Ohf GdTgQ hef GdTGeI Edi cRe fMh TgQ CjVkG s
(3bWYI efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1665s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs